Fragile phagocytes: FMRP positively regulates engulfment activity. - Logan, M.A. (Journal of Cell Biology, 2017)
Defective immune system function is implicated in autism spectrum disorders, including Fragile X syndrome. In this issue, O'Connor et al. (2017. J. Cell Biol. https://doi.org/10.1083/jcb.201607093) demonstrate that phagocytic activity of systemic immune cells is compromised in a Drosophila melanogaster model of Fragile X, highlighting intriguing new mechanistic connections between FMRP, innate immunity, and abnormal development.